Prevalence of HIV-Associated Metabolic Abnormalities among Patients Taking First-Line Antiretroviral Therapy in Uganda. (23rd August 2012) - Omech, Bernard; Sempa, Joseph; Castelnuovo, Barbara; Opio, Kenneth; Otim, Marcel; Mayanja-Kizza, Harriet; Colebunders, Robert; Manabe, Yukari C.
Abstract : Introduction . While the introduction of highly active antiretroviral therapy decreased HIV-related morbidity and mortality rates in the sub-Saharan Africa, a subsequent increase in metabolic abnormalities has been observed. We sought to determine the prevalence of HIV-associated metabolic abnormalities among patients on first-line antiretroviral therapy (ART) in an ART clinic in Kampala, Uganda. Methods . Four hundred forty-two consecutive patients on first-line ART for at least 12 months were screened for eligibility in a cross-sectional study, and 423 were enrolled. Pre-ART patient characteristics were abstracted from medical charts, examinations included anthropometric measurement and physical assessment for lipodystrophy. Results . The prevalence of hyperglycemia and dyslipidemia was 16.3% (69/423) and 81.5% (345/423), respectively. Prevalence of dyslipidemia between stavudine- and zidovudine-based regimens (91% versus 72%;P < 0.001 ). Being on stavudine (aOR 4.79, 95%, 2.45–9.38) and peak body weight (aOR 1.44, 95% CI 1.05–1.97) were independent risk factors for dylipidemia. Stavudine (aOR 0.50, 95% CI  0.27–0.93) use was associated with lower risk for hyperglycemia while, and older age (aOR 1.31, 95% CI 1.11–1.56) and having a family history of DM (aOR 2.18, 95% CI 1.10–4.34) were independent risk factors for hyperglycemia. Conclusions . HIV-associated metabolic complications were prevalent among patients on thymidine analogue-containing ART regimens. Screening for lipid and glucose abnormalities should be considered in ART patients because of cardiovascular risks.